Technology systematization and characterization of soil conservation practices in río Reventado's mid watershed, Cartago, Costa Rica - Suazo Cervantes, M.S. (CATIE, Turrialba (Costa Rica), 2014)
Ilus. 61 tab. Bib. p. 137-141.